Commodities and capabilities - "Sen, Amartya" (Delhi, 1987)
Commodities and Capabilities presents a set of inter-related theses concerning the foundations of welfare economics, and in particular about the assessment of personal well-being and advantage. The argument presented focuses on the capability to function, i.e. what a person can do or can be, questioning in the process the more standard emphasis on opulence or on utility. In fact, a person's motivation behind choice is treated here as a parametric variable which may or may not coincide with the pursuit of self-interest. Given the large number of practical problems arising from the roles and limitations of different concepts of interest and the judgement of advantage and well-being, this scholarly investigation is both of theoretical interest and practical import
Keywords: Commodities exchange